Associations of Childhood Neglect With the ACTH and Plasma Cortisol Stress Response in Patients With Type 2 Diabetes - Monzer, Nelly; Hartmann, Mechthild; Buckert, Magdalena; Wolff, Kira; Nawroth, Peter; Kopf, Stefan; Kender, Zoltan; Friederich, Hans-Christoph; Wild, Beate (Frontiers in Psychiatry, 2021)
Background Cross-sectional as well as longitudinal studies have linked childhood maltreatment to type 2 diabetes in adulthood with childhood neglect showing the strongest effect on type 2 diabetes risk. However, the mechanisms that link childhood maltreatment to type 2 diabetes are still unclear. Alterations in the psychological and physiological stress response system, specifically the hypothalamus-pituitary-adrenal (HPA) axis are a common finding in samples with a background of childhood neglect and are associated with type 2 diabetes. In the present study, we investigated the association between childhood neglect and the physiological and psychological stress response in patients with type 2 diabetes and healthy control participants. Method We assessed emotional and physical childhood neglect in a sample of n=74 patients with type 2 diabetes and n=50 healthy control participants. We used the trier social stress test (TSST) to induce a stress response. Blood ACTH and cortisol levels were measured before (T0), directly after (T1) as well as 30 (T2) and 60 (T3) minutes after the TSST. Participants’ subjective experience was assessed via visual analogue scales before, directly after as well as at 45 minutes after the TSST. We used multiple regression analyses to predict the change in self-reported tension between T0 and T1. Multilevel models were applied to predict cortisol and ACTH levels across all measurement points. Results We found a significant association between moderate to severe childhood neglect and a stronger psychological stress response in patients with type 2 diabetes, that was not present in healthy controls. In type 2 diabetes patients, but not in healthy controls, higher ACTH levels across all measurement points were significantly associated with higher severity of emotional neglect and higher severity of physical neglect was significantly associated with a stronger increase in plasma cortisol from T0 to T1. Conclusions This is the first study to investigate whether childhood maltreatment in patients with type 2 diabetes could be associated with a dysregulated stress response. Our results show a link between the psychological and physiological stress response and childhood neglect in type 2 diabetes patients. This pathway is a possible mechanism connecting type 2 diabetes and childhood neglect.